THE RELATION BETWEEN THE OBJECTIVE OF WTO AND ECONOMIC RIGHTS - Intan Innayatun Soeparna (Faculty of Law, Universitas Jenderal Soedirman, 2015)
WTO Members are obliged to provide trade rules and mechanism conducive for their citizens to conduct economy activities across frontier in order to pursue their economic interests. This obligation is based on economic rights that are granted in their national constitutions. It thus necessary to analyse the relation between the objective of WTO Agreements and economic rights in order to seek the clarity of the primary intention of WTO Members to conduct international trade under the WTO Agreements